Rancang Bangun Prototipe Sistem Pencitraan Bawah Tanah dengan Metode Electrical Resistence Tomography - Yunus Pebriyanto; Wilson Jefriyanto; Yoan Theasy; Yunita Enzelina Silaban; Salsa Ayudhia Pratama (Magnetic: Research Journal of Physics and It’s Application, 2026)
Electrical Resistivity Tomography (ERT) is a geophysical method used to image subsurface structures based on the distribution of material resistivity by injecting electrical current and measuring the resulting potential at the surface. Although widely applied in subsurface exploration, the use of ERT in academic environments is still limited due to the high cost of commercial equipment. Therefore, this study aims to design and develop a laboratory-scale prototype of a subsurface imaging system based on the ERT method as an educational and practical learning tool. The research employed a Research and Development (R&D) method combined with an experimental approach, including the stages of design, fabrication, testing, and calibration of the prototype. Experimental measurements were conducted on homogeneous soil media and soil media with artificial anomalies using Wenner and Wenner–Schlumberger configurations. The acquired data were processed using RES2DINV software to produce two-dimensional subsurface images. The results indicate that the developed prototype is capable of detecting resistivity anomalies effectively, although relatively high inversion errors were observed due to laboratory-scale limitations. Overall, the proposed ERT prototype is suitable as a supporting tool for geoelectrical learning and subsurface exploration practicum.